Resource Allocation in a PERT Network Under Continuous Activity Time-Cost Functions - Berman, E. B. (Management Science, 1964)
This paper describes a conceptual model which allocates resources in a PERT network, the activities of which are subject to continuous concave-upward time-cost functions, in such a way as to achieve a minimum cost solution for a given completion date for the program described by the network. A parametric solution for the minimum cost solution at various total program times is also briefly described. The effect of uncertainty in the time of completion of an activity has also been investigated in a highly simplified model; and a tentative conclusion is presented that such uncertainty tends to divert resources toward the earlier part of the program, as compared to the solution under certainty.